Examining determinants of corruption at the individual level in South Asia - Jinwon Han (Economies, 2023)
Although the topic of corruption in South Asia has attracted a great deal of attention, extant research on individual-level factors is sparse. With this background, this paper examines the effect of selected individual-level determinants on South Asian people's justifiability of corruption. For analysis, the paper uses the World Value Survey (WVS) dataset and carries out its own survey as well. Using multinomial logistic regression (MLR) and binomial logistic regression (BLR) as a robustness check, this paper identifies that variables of age, education, religiosity, and individualism/collectivism have significant effects on respondents' corruption justifiability in South Asia. In addition, the paper performs additional analyses independently using two surveys utilized in the main analysis as a single dataset to report the main differences between them. In conclusion, this paper proposes a region-specific suggestion for South Asian governments and policy makers.a
Keywords: 330; corruption; individual-level determinants of corruption; South Asia; multinomial logistic regression (MLR); binomial logistic regression (BLR)